Consumption of cariogenic foods with the presence of dental caries in schoolchildren in the Recôncavo da Bahia (Research, Society and Development, 2022)
The objective of this research was to investigate the association between the intake of cariogenic foods and the presence of dental caries in schoolchildren. A cross-sectional study was developed in a municipal school in Recôncavo da Bahia, where 167 children, aged 3 to 12 years, had their oral condition evaluated. Only parents/guardians of 66 children answered the questionnaire on socioeconomic and demographic characteristics and 40 answered the QFA. To evaluate the intake of sugary foods, the Food Frequency Questionnaire was used, and the presence of caries was evaluated using the CPO-D/ceo-d index. A questionnaire was applied to the caregivers to identify demographic and socioeconomic characteristics. The variables were submitted to bivariate analysis (Pearson's chi-square test) with a 5% significance level. The mean age of children was 6.8 years, with a predominance of mixed race/color (48.6%) and male (51.5%). As for the caretakers, 58.4% studied up to high school, 63.5% had an income of up to 1 minimum wage, and 97% lived in rural areas. The mean of CPO-D/ceo-d was 3.26 Children with caries had higher consumption of sugary foods. Dental caries showed statistically significant association with intake of fruit sweets (p